A novel method to simultaneously obtain multiple basic parameters for discretization-independent bond-based peridynamic analysis - Hu, Chaobin; Chen, Xiaomiao (Frontiers in Physics, 2025)
Peridynamics (PD) is an effective numerical analysis theory applicable to problems involving strong discontinuities such as fractures. The convergence of numerical results from PD models depends on multiple basic parameters such as the spatial discretization scale, horizon size, and time step size. However, there is a lack of a comprehensive research approach for verifying the independence of computational results from the discretization parameters, which may reduce the confidence of the numerical results. In the present work, a novel parameter independent verification method was proposed for the bond-based PD model. Based on the method, convergence studies on the Kalthoff-Winkler experiment was carried out to obtain the basic discretization parameters for the problem. The results indicate that the parameter independence verification method is effective. The study provides theoretical and technical supports for determining discrete parameters in numerical simulations.